Triangular Bezier patches in modelling smooth boundary surface in exterior Helmholtz problems solved by the PIES - ZIENIUK, Eugeniusz; SZERSZEŃ, Krzysztof (Archives of Acoustics, 2009)
The paper proposes the use of triangular parametric Bezier patches as a new and effective way to generate three-dimensional boundaries in acoustics problems. The boundary geometry composed of triangular Bezier patches has been directly linked to the parametric integral equation system (PIES) to numerical solving exterior Helmholtz problems. A primary advantage of the proposed approach is to avoid the necessity of conventional domain or boundary discretization. The obtained numerical solutions compared with literature exacts results are characterized by high accuracy and convergence.